UPBRINGING FUNCTION OF UNIVERSITY LIBRARY - Gramm, Olena M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
mportance of cultural-educational and upbringing activities of university libraries for upbringing of the student youth is highlighted.